Glucagon-Like Peptide-1 Receptor Agonists as Potential Myelination-Inducible and Anti-Demyelinating Remedies - Sango, Kazunori; Takaku, Shizuka; Tsukamoto, Masami; Niimi, Naoko; Yako, Hideji (Frontiers in Cell and Developmental Biology, 2022)
Glucagon-like peptide-1 receptor agonists (GLP-1RAs) were developed as insulinotropic and anti-hyperglycemic agents for the treatment of type 2 diabetes, but their neurotrophic and neuroprotective activities have been receiving increasing attention. Myelin plays a key role in the functional maintenance of the central and peripheral nervous systems, and recent in vivo and in vitro studies have shed light on the beneficial effects of GLP-1RAs on the formation and protection of myelin. In this article, we describe the potential efficacy of GLP-1RAs for the induction of axonal regeneration and remyelination following nerve lesions and the prevention and alleviation of demyelinating disorders, particularly multiple sclerosis.